2006
DOI: 10.1007/s00535-006-1806-1
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of plasma tissue factor levels in patients with severe acute pancreatitis

Abstract: Plasma TF levels were elevated in patients with SAP, particularly in those with alcoholic SAP with pancreatic necrosis, suggesting that TF may be closely related to the development of pancreatic necrosis in alcoholic SAP and that the plasma TF level may be a useful marker for it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 39 publications
(34 reference statements)
0
16
0
1
Order By: Relevance
“…Plasma levels of TF in AP patients have been shown to be higher than those of healthy volunteers, though there is no statistically significant difference in the TF levels between the severity groups of AP (Sawa et al, 2006). Plasma levels of TF in alcoholic severe AP with pancreatic necrosis was significantly higher than that in alcoholic severe AP without pancreatic necrosis or that in nonalcoholic s e v e r e A P w i t h p a n c r e a t i c n e c r o s i s .…”
Section: Coagulation and Fibrinolysis Abnormalities In Apmentioning
confidence: 92%
See 1 more Smart Citation
“…Plasma levels of TF in AP patients have been shown to be higher than those of healthy volunteers, though there is no statistically significant difference in the TF levels between the severity groups of AP (Sawa et al, 2006). Plasma levels of TF in alcoholic severe AP with pancreatic necrosis was significantly higher than that in alcoholic severe AP without pancreatic necrosis or that in nonalcoholic s e v e r e A P w i t h p a n c r e a t i c n e c r o s i s .…”
Section: Coagulation and Fibrinolysis Abnormalities In Apmentioning
confidence: 92%
“…This study along with others showed that platelets exert a proinflammatory response by invoking MIP-2 chemokine synthesis in pancreatic cells (macrophage and acinar cells) (Ramnath & Bhatia, 2006;Sun & Bhatia, 2007), a major signal for neutrophil infiltration and chemotaxis (Bhatia & Hegde, 2007;Li et al, 2004). Therefore targeting the inflammatory nature of platelets may have therapeutic potential in reducing pancreatic tissue injury and the severity of acute pancreatitis (Abdulla et al, 2011 2009;²Radenkovic et al 2004;³Mavrommatis et al 2000;Kinasewitz et al 2004;Collins et al 2006;Maeda et al 2006;Stief et al 2007;Lindstrom et al 2006;Sawa et al 2006;¹⁰Gando et al 1998;¹¹Powell et al 2001;¹²Ogura et al 2001;¹³Osmanovic et al 2000;¹ Lu et al 2007;¹ Yasuda et al 2009;¹ Uehara et al 2009;¹ Vinazzer et al 1988;¹ Ida et al 2009; †Denotes a non-significant value compared with normal controls. …”
Section: Targeting Platelet Activating Factor (Paf) and Platelets In Apmentioning
confidence: 99%
“…It was reported that necrotizing pancreatitis and inflammatory changes are related to its various complications and prognosis [4][5][6] . To improve its mortality, it is essential to accurately evaluate the grade of inflammation and the absence of necrotizing pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Patients suffering from acute pancreatitis (AP) often have additional complications such as sepsis, systemic inflammatory syndrome (SIRS) and multiple organ failure (MOF), resulting in a life-threatening condition [4][5][6] . Therefore, it is important to accurately evaluate the grade of inflammation and absence of necrotizing pancreatitis to improve its prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…The proinflammatory cytokines induce expression of tissue factor (TF), a glycoprotein that activates the extrinsic pathway of blood coagulation, on mononuclear and endothelial cells, providing a link between inflammation and hypercoagulation [7]. Accordingly, plasma TF levels are elevated in a variety of inflammatory conditions [8,9,10], including severe AP [11]. …”
Section: Introductionmentioning
confidence: 99%